Clinical Significance of Marma (Vital Points in Body) -A Review - Sharma, Prahalad Sahai; Sharma, Girdhar Gopal (International Research Journal of Ayurveda & Yoga, 2022)
The unique principle of Ayurveda is Marma Sharira. The Veda also makes mention of Marma (vital points in body). Aside from serving as anatomical landmarks, Marma are also the places where the Tridosha (basic elements of body) and its various forms, Prana, Ojasa or Soma, and Tejasa or Agni (vital elements of the body), are present. There are several disorders that come from harm to these Marma. Samhitas provide a clear definition of these illnesses’ ensuing signs and symptoms. Any lesion to these areas has the potential to cause death, excruciating pain, incapacity, loss of function, and loss of sensation. Therefore, it has been stated in the scriptures that even when doing procedures, these crucial places should not be damaged and should be left intact. According to recent studies, stimulating the Marma points close by can aid to reduce pain in Marma points that are inflamed or uncomfortable. The therapeutic advantages of Marma Therapy in treating a range of physical and mental illnesses have been recorded in several research and textbooks. The goal of this work is to give an Ayurvedic-based conceptual understanding of Marma.